Persepsi Pendidik PAUD terhadap Tes Masuk di Tingkat Sekolah Dasar - Fuadi, Noval (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
This study aims to describe the perception of Early Childhood Education educators on entrance tests at the elementary school level, including (a) Early Childhood Education Educators' knowledge of the concept of Early Childhood Education; (b) knowledge of Early Childhood Education educators on the implementation of entrance tests; and (c) the attitude of Early Childhood Education educators towards the implementation of entrance tests at the elementary school level. This research approach is a qualitative research with the type of case study research. As for the results of this study, firstly, from the aspect of knowledge of Early Childhood Education educators on the concept of Early Childhood Education, it is known that there are still Early Childhood Education educators who do not yet know the concept of Early Childhood Education; second, from the aspect of Early Childhood Education educators' knowledge of the implementation of the elementary school entrance test in Lhokseumawe City, it shows that in general, Early Childhood Education educators already know about the forms of tests, but the application of the tests used to see developments in children is still inaccurate and third, the perception of Early Childhood Education educators on the implementation of the entrance test at the elementary school level in the city of Lhokseumawe is that educators do not agree with the implementation. This is considered to be able to shift the concept of learning early childhood education actually.